Determinants for ICT Adoption and Problems: Evidence from Rural Based Small and Medium Enterprises in Malaysia - Jaganathan, Malaysia; Ahmad, Shuhymee; Ishak, Khairol Anuar; Mohd Nafi, Siti Noratisah; Uthamaputhran, Logeswari
The purpose of this study is to investigate the information and communication technology adoption among rural based SMEs in Malaysia and identify the problems facing these SMEs in the implementation and usage of ICT. In addition, the study also attempts to determine whether significant relationships exist between owners’ attitude, knowledge and innovativeness, and the ICT adoption. Questionnaire survey was used to obtain data from rural based SMEs in Malaysia. A total of 1000 questionnaires were distributed and 167 usable responses were received. The findings reveal a relatively high adoption of ICT among rural based SMEs while lack of funds and financing were the main problems to the success of its adoption and implementation. It was also found that only attitude had significant positive relationship with the ICT adoption. The findings of this study assist to owner/managers of rural based SMEs and also policy makers in Malaysia in finding strategies to cultivate culture of adopting and implementing of ICT for betterment of SMEs in Malaysia.